PKM Tools for Developing Personal Knowledge Management Skills among University Students - Rezvan Hosseingholizadeh; Atefeh Sharif; Masoumeh Kouhsari (International Journal of Information Science and Management, 2018)
This study aims to investigate how PKM tools support university students for developing personal knowledge management skills. It has been done based on the PKM Skill model developed by Avery, Brooks, Brown, Dorsey and O’Conner (2001) and Sharif and Hosseingholizadeh's (2016) PKM tools taxonomy. This research focuses on how PKM tools can support PKM skills in an academic environment. Data was collected from master's and PhD students of Ferdowsi University of Mashhad (FUM) (n=362). Results showed there is significant relationship between seven PKM skills and the use of PKM tools. The strength of the correlation is between the use of PKM tools and the securing, and analyzing skills. Also, the PKM skills play different and important role in awareness, being skilled in use of PKM tools and also the rate of usage. Some of PKM tools can be used by students to support their PKM skills. Moreover, results revealed that there is no significant relationship between usefulness and perceived ease of using and use of PKM tools. This necessity is felt more in the academic environments and among graduate students, since the nature of student's educational activities and research as knowledge worker, require skills of search, collect, transfer and sharing of information and knowledge.